G278(P) Development of a guideline for medical care of children with down syndrome, from a paediatric intensive care unit perspective. (25th October 2020) - Poole, R; De Munter, C
Abstract : Aims: Down syndrome (DS) is the most common genetic cause of cognitive disability, with a worldwide incidence between 1 in 1000 and 1 in 1100 live births. Children with DS have characteristic physical features, with an increased incidence of congenital or acquired medical conditions. The Down Syndrome Medical Interest Group (DSMIG) have produced guidance for essential basic medical surveillance in children with DS. Children with DS have also been shown to respond differently to critical illness, requiring a higher proportion of organ support than expected by initial disease severity. This project aimed to produce a hospital guideline for medical care of children with DS, whilst also taking into account specific considerations for care of a child with DS in PICU, to standardise and improve the quality of care. Methods: Involvement in medical care of children with DS admitted to PICU revealed that despite the availability of clear DSMIG guidance, there was no hospital guideline for children with DS. Furthermore, in terms of PICU care, key considerations were anecdotally noted, yet these differed between consultants and there was no PICU-specific guideline to outline a gold standard of care. DSMIG guidance was reviewed and PICU consultants approached for key specific considerations for care of a child with DS on PICU. A guideline was produced, edited and reviewed at a hospital guideline meeting, and agreed on by all PICU consultants. Results: Using DSMIG guidance, a hospital guideline could be produced for medical care of children with Down Syndrome, with additional specific requirements for PICU. Key PICU-specific considerations were noted and agreed on by a consultant team in terms of: airway; respiratory; cardiovascular; neurological; and infection. Conclusion: An admission to PICU can be a window of opportunity to ensure a child with DS is receiving the correct support from a multidisciplinary team, whilst there are also key PICU-specific considerations for their care. An SHO working under different leaders has an opportunity to develop a guideline to define and standardise a gold standard of care.